Temperature dependence calibration and correction of the DAMPE BGO electromagnetic calorimeter. (5th July 2016) - Wei, Y.F.; Zhang, Z.Y.; Zhang, Y.L.; Wen, S.C.; Wang, C.; Li, Z.Y.; Feng, C.Q.; Wang, X.L.; Xu, Z.Z.; Huang, G.S.; Liu, S.B.
Abstract: A BGO electromagnetic calorimeter (ECAL) is built for the DArk Matter Particle Explorer (DAMPE) mission. The temperature effect on the BGO ECAL was investigated with a thermal vacuum experiment. The light output of a BGO crystal depends on temperature significantly, and the readout system is also affected by temperature. The temperature coefficient of each BGO detection unit has been calibrated, and a correction method is also presented in this paper.